Impact of Russian Public Diplomacy and Soft Power in Sub-Saharan Africa: Shaping Influence in a Shifting Geopolitical Landscape (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This research examines the impact of Russia’s public diplomacy and soft power Sub-Saharan African countries. Methodologically, a combination of narrative research and ethnographic research designs has been applied. This includes both primary and secondary data collected from interviews, participant observation, case studies, comparative explorations, and archive data analysis. In so doing, the study looks into how Russian soft power affects views, influences policy choices, and promotes a favorable perception of Russia on the African continent. The study analyzes the historical evolution of Russia’s engagement with African countries; before assessing the contribution of the media outlets on diplomatic, economic, educational and cultural activities. Eventually, the study demonstrated that the media outlets contribute significantly in creating a positive perception of Russia in Sub-Saharan Africa, eliminating the biases related to African societies, and ultimately increasing trust in the bilateral cooperation process.